Functional connectivity changes following interpersonal reactivity. Issue 2 (21st November 2017) - Krause, A. L.; Colic, L.; Borchardt, V.; Li, M.; Strauss, B.; Buchheim, A.; Wildgruber, D.; Fonagy, P.; Nolte, T.; Walter, M.
Abstract: Attachment experiences substantially influence emotional and cognitive development. Narratives comprising attachment‐dependent content were proposed to modulate activation of cognitive‐emotional schemata in listeners. We studied the effects after listening to prototypical attachment narratives on wellbeing and countertransference‐reactions in 149 healthy participants. Neural correlates of these cognitive‐emotional schema activations were investigated in a 7 Tesla rest‐task‐rest fMRI‐study (23 healthy males) using functional connectivity (FC) analysis of the social approach network (seed regions: left and right Caudate Nucleus, CN). Reduced FC between left CN and bilateral dorsolateral prefrontal cortex (DLPFC) represented a general effect of prior auditory stimulation. After presentation of the insecure‐dismissing narrative, FC between left CN and bilateral temporo‐parietal junction, and right dorsal posterior Cingulum was reduced, compared to baseline. Post‐narrative FC‐patterns of insecure‐dismissing and insecure‐preoccupied narratives differed in strength between left CN and right DLPFC. Neural correlates of the moderating effect of individual attachment anxiety were represented in a reduced CN‐DLPFC FC as a function of individual neediness‐levels. These findings suggest specific neural processing of prolonged mood‐changes and schema activation induced by attachment‐specific speech patterns. Individual desire for interpersonal proximity was predicted by attachment anxiety and furthermore modulated FC of the social approach network in those exposed to such narratives.